SOSIALISASI FUNGSI EKOLOGIS MANGROVE PADA MASYARAKAT PESISIR DESA BAKA JAYA, KECAMATAN WOJA, KABUPATEN DOMPU: SOSIALISASI FUNGSI EKOLOGIS MANGROVE PADA MASYARAKAT PESISIR DESA BAKA JAYA, KECAMATAN WOJA, KABUPATEN DOMPU - Awan Dermawan (Jurnal Pengabdian Perikanan Indonesia, 2025)
The mangrove ecosystem plays a crucial role in maintaining the balance of the coastal environment, both ecologically and economically. However, overexploitation and a lack of public understanding have led to the degradation of mangrove ecosystems in various coastal areas, including in Baka Jaya Village, Woja District, Dompu Regency. This community service activity aims to enhance public understanding of the ecological functions of mangroves and provide education on the importance of mangrove conservation for environmental sustainability and the well-being of coastal communities. The methods used include lectures and interactive discussions with the community. Evaluation results indicate an increase in public understanding of the ecological functions of mangroves and a rise in community participation in conservation efforts. This activity is expected to contribute to the sustainable preservation of the mangrove ecosystem.